Arrhythmogenicity of anti-tachycardia pacing programming parameters in patients with structural heart disease and implantable defibrillators - Sherien Samy Awad (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Anti-tachycardia pacing therapy (ATP) is an effective, painless therapy for ventricular tachycardia (VT) termination. However, some patients experience VT acceleration that might degenerate into ventricular fibrillation (VF), leading to shock therapy. The aim of the study was to investigate the incidence of VT acceleration in patients with structural heart disease and implantabledefibrillators and its relation to the ATP programming parameters.Methods: A total of 448 monomorphic VT episodes in 60 patients with structural heart disease and an ICD implant were reviewed after being retrieved from the programmers. The patients’ clinical data and the episodes’ details were analysed.Results: ATP therapy was successful in terminating the VT in 70% of the analysed episodes. The incidence of VT acceleration in our studied patients was 8.5%. Patients with accelerated VT had a lower ejection fraction compared to patients with ATP-successful episodes. In the accelerated episodes, ramp pacing and scanning were frequently turned on. When VT-accelerated episodes werecompared to ATP-successful ones, the number of ATP bursts was higher and the adaptive cycle length was shorter.Conclusions: Ventricular tachycardia acceleration by ATP therapy is likely to occur in patients with a severely impaired ejection fraction. Scanning, ramp pacing, and the number of ATP bursts delivered had a significant effect on VT acceleration. Scanning and ramp pacing are better to be turned off, and a lesser number of ATP bursts with a longer adaptive CL should be delivered.